A comprehensive study on the performance of vertical ground-coupled heat pumps. (May 2023) - Moghanni, Reza; Hakkaki-Fard, Ali; Hannani, Siamak Kazemzadeh
Highlights: A detailed heat pump model and an accurate analytical VGHE model are developed. The long-term effects of various factors on VGCHP performance are investigated. Numerous cases of VGCHP system are simulated and their sensitivity is analyzed. The heat pump type is the most influential parameter on the COP of the VGCHP system. The climate type is the most influential parameter on the qmax . Abstract: Vertical Ground-Coupled Heat Pump (VGCHP) systems are a green and sustainable alternative to conventional heating, ventilating, and air-conditioning systems. However, their main drawback is the high initial installation cost of the Vertical Ground Heat Exchanger (VGHE), which has hindered their widespread adoption. Improving the performance of VGCHP to reduce their installation and operating costs requires a comprehensive study that scrutinizes the long-term effects of various involving parameters on the performance of the system. This contribution presents a comprehensive study investigating various influential factors, including climate type, refrigerant type, borehole depth, and type of compressor and circulating pump, on the VGCHP system performance. For this aim, a detailed model of the VGCHP is developed that includes detailed heat pump modeling, fast and accurate VGHE analytical modeling, and recommended constraints of the ASHRAE standard. The developed heat pump model is compatible with both pure and refrigerant mixtures. The five-year operation of 180 cases is simulated. Based on five-year simulation results and sensitivity analysis, 90 cases are selected, and their 20-year operation is investigated. The results demonstrated that the heat pump type is the most influential parameter on the Coefficient of Performance (COP), and the climate type is the most influential parameter on the maximum thermal load provided to the building per VGHE unit length. Moreover, optimum design parameters are determined based on short- and long-term simulation results. Furthermore, the response surface method is implemented to develop predictive equations for COP and maximum thermal load as a function of influential factors.